KEPEMIMPINAN KOMUNIKATIF HENDRIK LEWERISSA: MEMBANGUN KESEJAHTERAAN SOSIAL MELALUI REVITALISASI NILAI PAR MALUKU PUNG BAE - Hobarth Williams Soselisa; Rido Dominggus Latuheru (JURNAL BADATI, 2025)
This study analyzes the communicative leadership of Governor Hendrik Lewerissa in revitalizing Par Maluku Pung Bae values to build social welfare in Maluku Province. Using a qualitative approach with case study design, this research examines policy documents, public statements, and socio-economic development reports from 2019-2024. The findings reveal that communicative leadership integrating local wisdom values creates effective mechanisms for community participation in development. Par Maluku Pung Bae core values—O'dora (mutual love), O'baliara (mutual care), and O'adili (justice)—are implemented through inclusive dialogue, culturally-based communication, and empowerment programs. This leadership approach successfully enhances social welfare through poverty alleviation programs, improved access to education and healthcare, and strengthened social cohesion in post-conflict contexts. The research concludes that value-based communicative leadership serves as an alternative development model that is contextually relevant and sustainable, offering theoretical contributions to local wisdom-based leadership literature and practical implications for regional development policies in Indonesia's eastern regions.